Free Amine, Hydroxyl and Sulfhydryl Directed C−H Functionalization and Annulation: Application to Heterocycle Synthesis. Issue 2 (26th August 2021) - Kumar, Sandeep; Kumar, Akshay; Sharma, Dharminder; Das, Pralay
Abstract: Transition metal‐catalyzed direct C−H bond functionalization is recognized as an efficient strategy to assemble heterocyclic frameworks. For this purpose, directing groups (DGs) installation on an organic molecule has remained a widely exploited strategy for the years. The installation of directing groups, especially for the amine, alcohol and thiol containing reactants and their removal after the reaction need additional steps. In this regard, the use of free amine, hydroxyl and sulfhydryl as directing groups in native form is advantageous and in recent times, these transformations have stirred undisputable advancements for applications to heterocycle synthesis. In this review, the aromatic sp 2 ‐C attached free amine, hydroxyl and sulfhydryl as native functionalities are shown to be useful for the construction of five to seven‐membered N ‐, O ‐ and S ‐heterocycles. Abstract : This review focuses on the application of free amine, hydroxyl and sulfhydryl directed C−H functionalization and annulation to synthesize N, O and S‐ heterocycles. The reaction design, scope and mechanistic features are thoroughly discussed.